Artificial Intelligence and the Future of Teachers: Redefining Roles in the Digital Era - Laila Fitri; Mhd. Kurniawan; A. Masrurah Aswidyaningrat; Muhammad Sabri Latif; Al- Mahdi (IAIN Manado, 2026)
The rapid development of artificial intelligence (AI) has transformed the educational landscape through applications such as adaptive learning systems, intelligent tutors, chatbots, and learning analytics. While these innovations enhance learning effectiveness, efficiency, and personalization, they also raise important questions regarding the future role of teachers in education. This study aims to analyze the forms of AI implementation in learning, examine their implications for teachers’ roles and professional identities, and propose strategies for fostering a collaborative relationship between AI and educators. Using a literature review method with a critical analysis of recent national and international studies, the research finds that AI offers significant opportunities to support teaching and learning processes. However, its integration also presents challenges, including the potential dehumanization of education, ethical concerns, privacy issues, and the need to redefine teachers’ professional functions. To address these challenges, the study highlights the importance of strengthening teachers’ AI literacy, developing human-centered curricula, implementing ethical governance frameworks, and positioning teachers as guardians of human values and character development. The study concludes that AI should function as a strategic partner rather than a substitute for teachers and recommends multidisciplinary collaboration in designing equitable, inclusive, and ethically grounded AI-based education policie